2021
DOI: 10.1108/tr-03-2021-0165
|View full text |Cite
|
Sign up to set email alerts
|

Perceived COVID-19 impacts and travel avoidance: application of protection motivation theory

Abstract: Purpose The COVID-19 pandemic and the travellers’ behaviour towards travel risk is an emerging issue. Nonetheless, the travellers’ perceived COVID-19 impacts, travel risk perception, health and safety perception and travel avoidance concerning protection motivation theory is unnoticed. Following the protection motivation theory, the current study investigates the direct and indirect relationships between perceived COVID-19 impacts and travel avoidance. Moreover, the travellers’ cognitive perceptions of risk ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 39 publications
(54 reference statements)
2
31
1
1
Order By: Relevance
“…Additionally, Reisinger and Mavondo (2005) identified that the mediating role of perceived safety in the relationship between the anxiety of tourists and travel intentions. Meanwhile, in the context of Covid-19, by applying the PMT, Nazneen, Xu, Din, and Karim (2021) found that travel risk perception and safety perception can moderate the relationship between the perceived Covid-19 impacts and travel avoidance. Accordingly, travelers evaluated the seriousness of travel hazards and took precautions, which affected their travel behavior and resulted in travel avoidance in Covid-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Reisinger and Mavondo (2005) identified that the mediating role of perceived safety in the relationship between the anxiety of tourists and travel intentions. Meanwhile, in the context of Covid-19, by applying the PMT, Nazneen, Xu, Din, and Karim (2021) found that travel risk perception and safety perception can moderate the relationship between the perceived Covid-19 impacts and travel avoidance. Accordingly, travelers evaluated the seriousness of travel hazards and took precautions, which affected their travel behavior and resulted in travel avoidance in Covid-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant tourism literature predominantly attributes protective travel behaviors during the pandemic to the threat appraisals and risks perceptions of COVID-19 ( Bhati et al, 2021 ; Chua, Al-Ansi, Lee, & Han, 2021 ; Nazneen, Xu, Din, & Karim, 2021 ), as well as the emotional reactions predisposed to such threats ( Luo & Lam, 2020 ; Zenker, Braun, & Gyimóthy, 2021 ; Zheng et al, 2021 ). While the role of negative emotions such as fear and anxiety has been emphasized for their influences on travel propensity ( Kim, Yang, et al, 2021 ; Luo & Lam, 2020 ; Rather, 2021 ; Zenker et al, 2021 ; Zheng et al, 2021 ), the presumption of this direct causation is subject to criticism of oversimplification fallacy.…”
Section: Introductionmentioning
confidence: 99%
“…Table 7 shows that this influence path hypothesis was valid, demonstrating that psychological factors affected travel behavior decisions. As with previous travel behavior studies, this is a valid conclusion, but it still failed to establish a cause-and-effect relationship between the built environment and behavior [ 8 , 32 , 33 ]. Building on Model A, Model B incorporated subjective and environmental factors as exogenous latent variables, expanded the basic framework of the TPB, and established the influence path of “environment-perception-behavior”.…”
Section: Discussionmentioning
confidence: 62%